A proposal of calligraphy learning assistant system with letter portion practice function using projection mapping. Issue 2 (22nd October 2019) - Huda, Samsul; Funabiki, Nobuo; Kuribayashi, Minoru; Kao, Wen-Chung
Abstract : Purpose: For several decades, calligraphy has been popular among people in Japan, China, and even in the world. Traditionally, a teacher teaches how to write letters on a paper with a brush, and a student will imitate them by referring to the model letters. However, if a teacher is not available, this method will not be applicable either. This study aims to propose a calligraphy learning assistant system (CLAS) using projection mapping, which allows a student to learn calligraphy by him/herself. Design/methodology/approach: By following the letter writing video of a teacher that is directly projected on the paper, a student is able to learn the stroke order and writing speed in addition to the letter shape. Moreover, the letter portion practice function is incorporated in CLAS to allow a learner to repeat practicing hard portions of each letter. Findings: For evaluations, the authors implemented CLAS using Raspberry Pi and open-source software and asked students to use it. The results confirmed that CLAS is effective in improving calligraphy skills of novice students. Originality/value: With CLAS, a student can practice calligraphy using a conventional brush, ink and paper at a desk while looking at the model letter writing of a teacher projected on the paper using projection mapping.